Understanding young adults' perceptions regarding human papillomavirus vaccination: A qualitative study. - Oluwafemifola Oyedeji; Carman North; Kristina W Kintziger; Samantha Ehrlich; Jill Maples; Justin Gatwood; Cristina S Barroso (PLoS ONE)
Background Over 47,000 human papillomavirus (HPV) related cancers are newly diagnosed every year in the United States, yet HPV vaccination rates are below desirable levels. Young adulthood is critical for catch-up HPV vaccination. Previous research on HPV vaccine-seeking behavior among young adults is limited, particularly in Tennessee. This study aimed to understand HPV vaccine perceptions and experiences of young adults. Methods Virtual semi-structured interviews were conducted among 18-26-year-olds at a university in Tennessee from April to May 2022 (N = 25). Interview questions were based on the Health Belief Model and previous literature with a focus on gaining in-depth insights into young adults' perspectives regarding HPV vaccination. Inductive and deductive thematic analysis approaches were used for data analysis. Results Five major themes were identified: (1) perceptions about HPV and HPV vaccination, (2) factors that may prevent HPV vaccination, (3) role of health care providers, (4) role of family and friends, and (5) HPV vaccine promotion strategies. Participants commonly discussed lack of knowledge and awareness as a factor preventing HPV vaccine uptake. Participants described some facilitators of HPV vaccination, including healthcare provider recommendations and family support, and perceived future benefits of receiving the HPV vaccine. Suggestions for promotion strategies included promotion through college health centers, community education, and awareness campaigns. Conclusions Young adults' perceptions about the HPV vaccine and inadequate knowledge may influence uptake. Findings from this study showed that healthcare provider recommendations and parental support were facilitators for getting vaccinated. Future efforts may consider increasing awareness among young adults, exploring barriers to recommendation, and addressing parental concerns.